THE INFLUENCE OF THE SILENT WAY METHOD IN INCREASING STUDENTS' AWARENESS OF THE IMPORTANCE OF LEARNING ARABIC - Sinaga, Emi Salsabila; Setiyawan, Agung (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to determine the effect of the Silent Way method on increasing students' awareness of the importance of learning Arabic. The background of this study is based on the low awareness of students in understanding Arabic language learning as a strategic tool in global communication and career development. The method used was a quasi-experiment with a nonequivalent control group design, involving 40 students divided into an experimental group and a control group. The experimental group received instruction using the Silent Way method, while the control group used conventional methods. The research instrument was a Likert scale questionnaire measuring the cognitive, affective, and conative dimensions of learning awareness, analyzed using a t-test. The results showed a significant increase in the experimental group (average score increased from 2.9 to 3.7) compared to the control group (from 2.6 to 2.8), with a p-value 0.001. These findings prove that the Silent Way method is effective in fostering learning awareness through participatory, reflective, and learner-centered learning. This study recommends the application of this method in Arabic language instruction as an innovative strategy for building students' intrinsic awareness.